Development of Novel Bioreactor Control Systems Based on Smart Sensors and Actuators - Wang, Baowei; Wang, Zhiwen; Chen, Tao; Zhao, Xueming (Frontiers in Bioengineering and Biotechnology, 2020)
Bioreactors of various forms have been widely used in environment protection, healthcare, industrial biotechnology and space exploration. Robust demand in the field stimulated the development of novel design of bioreactor geometries, process control strategies and evolution of physical structure of the control system. After the introduction of digital computers to bioreactor process control, a hierarchical structure control system (HSCS) of bioreactors has become the dominant physical structure with high efficiency and robustness. However, inherent drawbacks of the HSCS of bioreactors have produced a need for a more consolidated solution of the control system. With the fast progresses in sensors, machinery and information technology, the developing of a flat organizational control system (FOCS) of bioreactors based on parallel distributed smart sensors and actuators may provide a more concise solution for process control in bioreactors. Here, we reviewed the evolution of the physical structure of bioreactor control systems and discussed the properties of the novel FOCS of bioreactors, related smart sensors, actuators and their application circumstances, with the hope of further improving the efficiency, robustness and economics of bioprocess control.